Modeling the Way Strategy to Improve Student Activities and Learning Outcomes in Islamic Education Learning at Ie Seuum Elementary School - Marlina; Rosnawati (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the activity and ability to perform obligatory prayers in students through the modeling the way strategy. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were the activity and ability to perform obligatory prayers of grade III students of SD NEGERI IE SEUUM, with a total of 25 students. The data for this study were obtained using test techniques and non-test techniques. The data analysis techniques used in this study were documents, tests and observations. The results showed that the Modeling the Way strategy was effective in improving the activity and ability of grade III students of SD Negeri Ie Seuum in performing obligatory prayers. With the role of teachers and peers as models, students showed increased discipline, technical skills, and understanding of prayer. In addition, the habit of praying that was reinforced at school also had a positive impact on the family environment, where parents reported changes in children's behavior in reminding and inviting other family members to pray.